Thyrotropin serum levels are differentially associated with biochemical markers of bone turnover and stiffness in women and men: results from the SHIP cohorts. Issue 2 (February 2016) - Tsourdi, E.; Wallaschofski, H.; Rauner, M.; Nauck, M.; Pietzner, M.; Rettig, R.; Ittermann, T.; Völzke, H.; Völker, U.; Hofbauer, L.; Hannemann, A.
Abstract Summary In two large German population-based cohorts, we showed positive associations between serum thyrotropin (TSH) concentrations and the Fracture Risk Assessment score (FRAX) in men and positive associations between TSH concentrations and bone turnover markers in women. Introduction The role of thyroid hormones on bone stiffness and turnover is poorly defined. Existing studies are confounded by differences in design and small sample size. We assessed the association between TSH serum concentrations and bone stiffness and turnover in the SHIP cohorts, which are two population-based cohorts from a region in Northern Germany comprising 2654 men and women and 3261 men and women, respectively. Methods We calculated the bone stiffness index using quantitative ultrasound (QUS) at the calcaneus, employed FRAX score for assessment of major osteoporotic fractures, and measured bone turnover markers, N-terminal propeptide of type I procollagen (P1NP), bone-specific alkaline phosphatase (BAP), osteocalcin, and type I collagen cross-linked C-telopeptide (CTX) in all subjects and sclerostin in a representative subgroup. Results There was no association between TSH concentrations and the stiffness index in both genders. In men, TSH correlated positively with the FRAX score both over the whole TSH range (p < 0.01) and within the reference TSH range (p < 0.01). There were positive associations between TSH concentrations and P1NP, BAP, osteocalcin, and CTX (p < 0.01) in women but not in men. There was no significant association between TSH and sclerostin levels. Conclusions TSH serum concentrations are associated with gender-specific changes in bone turnover and stiffness.